THE INFLUENCE OF MARKETING MIX, STORE IMAGE, STORE ATMOSPHERE, SHOPPING EXPERIENCE ON BUYING INTEREST OF TRANSMART CARREFOUR INDONESIA CONSUMER - Furqan , Muhammad; Yuliati , Lilik Noor; Indrawan , Dikky (International Journal of Artificial Intelligence for Digital Marketing, 2024)
The retail business in Indonesia, especially modern retail, is growing quite rapidly. Transmart Carrefour is now a brand that is widely known and recognized by the public by getting the highest TBI (Top Brand Index) score compared to others. The purpose of this study is to analyze the influence of marketing mix, store image, store atmosphere, shopping experience on consumer purchasing interest at Transmart Carrefour Indonesia. The approach used in this study is a quantitative approach with an online survey method to respondents. The population in this study is people who have made purchases at Transmart Carrefour throughout Indonesia. The number of samples used in research using Partial least squares-SEM analysis is at least 30-100 samples. So the researcher decided to use a sample of 100 consumers. The results of the study show that, 1). There is a significant positive influence of marketing mix on purchase interest. The mean value (average) is 4.345. This result indicates that the marketing mix at Transmart Carrefour has been running very well. 2). There is a significant positive influence of store image on purchase interest. The mean value (average) is 4.159. This result indicates that store image at Transmart Carrefour has been running well 3). There is a significant positive influence of store atmosphere on purchase interest. The mean value (average) is 3.934. This result indicates that the store atmosphere at Transmart Carrefour has been running quite well, 4). This result indicates that the store atmosphere at Transmart Carrefour has been running quite well. 4). There is a significant positive influence of shopping experience on purchase interest. The mean value (average) is 4.075. This result indicates that the shopping experience at Transmart Carrefour has been running well.